2016
DOI: 10.1371/journal.pgen.1006116
|View full text |Cite
|
Sign up to set email alerts
|

Super Resolution Fluorescence Microscopy and Tracking of Bacterial Flotillin (Reggie) Paralogs Provide Evidence for Defined-Sized Protein Microdomains within the Bacterial Membrane but Absence of Clusters Containing Detergent-Resistant Proteins

Abstract: Biological membranes have been proposed to contain microdomains of a specific lipid composition, in which distinct groups of proteins are clustered. Flotillin-like proteins are conserved between pro—and eukaryotes, play an important function in several eukaryotic and bacterial cells, and define in vertebrates a type of so-called detergent-resistant microdomains. Using STED microscopy, we show that two bacterial flotillins, FloA and FloT, form defined assemblies with an average diameter of 85 to 110 nm in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
(102 reference statements)
7
40
0
Order By: Relevance
“…Insertion of the transposon into three other loci including the gene floT , encoding the flotillin homolog FloT, the fliG gene, encoding the flagellar rotor protein FliG, and the flhA gene, encoding a component of flagellar type III export apparatus FlhA, exhibited a non-uniform or punctate localization at the membrane. We note that the localization pattern is consistent with previous observations in that FloT was reported to have a punctate localization (36), and FliG (37) and FlhA (38) are integral parts of the flagellar basal body that also localizes as puncta (39). We conclude that TnFLXgfp can randomly generate translational fusions within an open reading frame and can reproduce subcellular localization patterns that have been reported previously.…”
Section: Resultssupporting
confidence: 91%
“…Insertion of the transposon into three other loci including the gene floT , encoding the flotillin homolog FloT, the fliG gene, encoding the flagellar rotor protein FliG, and the flhA gene, encoding a component of flagellar type III export apparatus FlhA, exhibited a non-uniform or punctate localization at the membrane. We note that the localization pattern is consistent with previous observations in that FloT was reported to have a punctate localization (36), and FliG (37) and FlhA (38) are integral parts of the flagellar basal body that also localizes as puncta (39). We conclude that TnFLXgfp can randomly generate translational fusions within an open reading frame and can reproduce subcellular localization patterns that have been reported previously.…”
Section: Resultssupporting
confidence: 91%
“…Although we cannot exclude that flotillins may affect PBPs that are not easily detected by Bocillin-FL, our results do not provide any evidence for a role for flotillins in the oligomerization of PBPs in B. subtilis . This extends the finding of the Graumann lab that found either transient or no colocalization between flotillins and other proteins present in DRM fractions 30 . Although it is obvious that peptidoglycan synthesis is altered in the absence of flotillins, our data strongly suggest that the basis for this alteration is in the physical organisation of the membrane rather than inefficient formation of divisome or elongasome complexes in the absence of flotillins, because flotillin mutants strains show no synthetic phenotype on minimal medium, and the defects on rich medium can be reverted by chemically fluidizing the membrane.…”
Section: Discussionsupporting
confidence: 90%
“…FloA is constitutively expressed, whereas FloT is expressed primarily during stationary growth, cell wall stress and sporulation 27-29 . Super resolution microscopy showed that the flotillins and other proteins found in DRMs do not colocalize and have different dynamics 30 , so it is unlikely that FMMs are regions in the membrane that offer a favourable environment in which these membrane proteins are continuously present and active. Recently, the hypothesis has been put forward that FMMs/flotillins form a platform for the formation of functional protein oligomers, as work in Staphylococcus aureus showed that multimerization of Type 7 secretion systems and PBP2a depends on FMMs 19,20,31 .…”
Section: Introductionmentioning
confidence: 99%
“…As described above, our data suggest that ACC (AccA‐GFP) localizes on or near the membrane as punctate foci, similar to FloA and FloT (Dempwolff et al ., ). Considering both these observations and the ACC enzyme's essential role in the synthesis of fatty acids and membrane lipids (Pedrido et al ., ), we wondered whether the distribution of punctate AccA‐GFP signals might be dependent on FloA and/or FloT.…”
Section: Resultsmentioning
confidence: 97%
“…In the membranes of mammalian cells, membrane proteins called Flotillins are considered to be scaffold proteins that help localize other membrane proteins to specific membrane areas, such as lipid rafts (Stuermer, 2011). Two flotillin-like proteins, FloT and FloA have been identified in bacterial membranes (Lopez and Kolter, 2010) and are proposed to serve a similar purpose (Bodin et al, 2014;Bramkamp and Lopez, 2015;Lopez and Koch, 2017), though another study argues that FloTA do not function as scaffold proteins (Dempwolff et al, 2016).…”
Section: Membrane Localization Of Accda Is Independent Of Flotillin-lmentioning
confidence: 99%